ADMINISTRATIVE LAW PROTECTIVE FUNCTION THEORETICAL-LEGAL ANALYSIS - Миронець, Оксана Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: in the article theoretical and legal aspects of a protective function of Administrative Law have been analyzed; attention has been focused on its concept and attributes. Methods: dialectical, as well as logical methods: analysis, comparison, generalization. Results: the concept and types of a protective function of Administrative Law have been clarified, its attributes have been considered. Discussion: the concept and preventive, discontinuing, restorative, ensuring the bringing to administrative liability and imposition of administrative penalty nature of the protective function of Administrative Law. A protective function of Administrative Law, in our opinion, is the direction of this field of law influence, which has its preventive, interrupting, restorative, ensuring the bringing to administrative liability and the imposition of administrative penalties nature. Attributes of this function of Administrative Law are: 1) the permanence of preventive influence on social relations, which constitute the subject of legal regulation of this field of law;2) the situational nature of the use of coercive, restorative and suppressive influence on subjects of social relations, which constitute the subject of legal regulation of the field of law;3) the specific nature of ensuring the bringing to administrative liability;4) the possibility of variation in the application of measures of influence and administrative penalties, depending on the age criterion of a subject of an administrative offence. Types of a protective function of Administrative Law can be preventive and security, which in turn can be divided into punitive and restorative.We think that in the context of understanding the function exercised by Administrative Law to ensure the proper implementation of its subjects’ rights, freedoms and obligations in conditions of their lawful and unlawful behaviour, the meaning of protective and security functions is identical. We keep in mind that considering the first one only as protection in sense of preventive or the second one in the sense of bringing to legal liability is too narrow of its understanding. In our opinion, the protection of rights, freedoms, that is, the performing of the protective function by law is carried out not passively as a preventive mechanism of non-interference control of social institutions that under their lawful implementation, which is more likely to reveal the preventive function of law, but not the protective. We believe that the protective function of Administrative Law acts both in the lawful and unlawful “environment” for the implementation of rights, freedoms, prohibitions and obligations of the subjects of administrative-legal relations. In the first case, its nature is preventive, since the very existence of the rules of Administrative Law on those or other prohibitions for their observance, a procedure for the use of rights and fulfillment of duties, as well as measures of administrative warning, measures of administrative discontinuing, administrative penalties, as well as measures to ensure the proceedings on administrative offences and administrative restoration measures already has a protective influence on the subjects of administrative-legal relations. In the second case, it is a reaction to non-compliance with prohibitions, violations of the order to use rights or fulfilment or, in general, non-fulfilment of duties.